A neuroscience perspective on sexual risk behavior in adolescence and emerging adulthood - VICTOR, ELIZABETH C. (Dev Psychopathol, 2015)
Late adolescence and emerging adulthood (specifically ages 15–24) represent a period of heightened sexual risk taking resulting in the greatest annual rates of sexually transmitted infections and unplanned pregnancies in the US population. Ongoing efforts to prevent such negative consequences are likely to benefit from a deepening of our understanding of biological mechanisms through which sexual risk taking emerges and biases decision making during this critical window. Here we present a neuroscience framework from which a mechanistic examination of sexual risk taking can be advanced. Specifically, we adapt the neurodevelopmental triadic model, which outlines how motivated behavior is governed by three systems: approach, avoidance, and regulation, to sexual decision making and subsequent risk behavior. We further propose a testable hypothesis of the triadic model, wherein relatively decreased threat-related amygdala reactivity and increased reward-related ventral striatum reactivity leads to sexual risk taking, which is particularly exaggerated during adolescence and young adulthood when there is an overexpression of dopaminergic neurons coupled with immature top-down prefrontal cortex regulation. We conclude by discussing how future research based on our adapted triadic model can inform ongoing efforts to improve intervention and prevention efforts.